ANALISIS IMPLEMENTASI ADMINISTRASI PENDIDIKAN DENGAN SISTEM INFORMASI MANAJEMEN AKADEMIK BERBASIS TEKNOLOGI DI PAUD - Indah Afrilia Hasibuan; Armanila, Salsabila Siregar, Ririn Widayanti, Hotma Sari Harahap (Adisam Publisher, 2023)
This research describes the implementation of the Academic Information System at Ulul Ilmi Kindergarten as an effort to improve administrative efficiency and learning quality. Qualitative methods were used to explore the impact of using this system from the perspectives of teachers, students, and administrative staff. The research results show increased efficiency in recording attendance, schedule management, and managing student data. Reduction in manual errors as well as accelerated reporting through this system were also observed. In addition, an evaluation of the impact on the quality of teaching and learning shows significant improvements. Academic Information Systems are proven to bring positive changes in the early childhood education environment.